Methods and Means of Developing Professional Competence Qualities of Teachers in Training Using Uzbek Folk Pedagogy - Saidmuradova Sitora Nabijonovna (Journal of Geography, Regional Planning and Development, 2024)
In this state, the importance of using Uzbek national pedagogy and education of professional-competent qualities of pedagogues and raising qualifications, self-image of education of professional-moral qualities of pedagogues, na osno natsionalnyx traditional, customs and tradition of the Uzbek nation "Vospitanie professionalnyx khaestv u pedagogov, na osno idey narovnoy pedagogiki osveshchatsya" soderjanie vospitaniya professional-tvorcheskih knobnostey pedagogov.